2022
DOI: 10.1039/d2bm00505k
|View full text |Cite
|
Sign up to set email alerts
|

Mild phototherapy mediated by manganese dioxide-loaded mesoporous polydopamine enhances immunotherapy against colorectal cancer

Abstract: The application of MnO2@MPDA-PEG NPs for reshaping the tumor microenvironment under mild PTT inhibits tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…After accumulating in colorectal tumors, MnO 2 NPs were reduced to Mn 2+ in TME, which could be further used as the MRI contrast agent for tumor imaging. 148 The light in first NIR optical window (NIR-I, 750-1000 nm) is mainly used in PTT. However, the depth of the penetration limits its efficacy to a certain extent.…”
Section: Immunotherapy Combined With Photothermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…After accumulating in colorectal tumors, MnO 2 NPs were reduced to Mn 2+ in TME, which could be further used as the MRI contrast agent for tumor imaging. 148 The light in first NIR optical window (NIR-I, 750-1000 nm) is mainly used in PTT. However, the depth of the penetration limits its efficacy to a certain extent.…”
Section: Immunotherapy Combined With Photothermal Therapymentioning
confidence: 99%
“…This indicated that the NPs could cooperate with the mild photothermal effect to enhance the anti-tumor immunity of the body. 148 However, existing photothermal immunotherapy is limited by the complexity of TME and the depth of tissue penetration of light. To improve the effectiveness of combination therapy, Li and colleagues proposed a strategy of combining Mn 2+ with PTT, which could promote CDT and maximize the ICD of tumors.…”
Section: Immunotherapy Combined With Photothermal Therapymentioning
confidence: 99%
“…Li et al. reported MnO 2 @MPDA-PEG nanoparticles, through the incorporation of MnO 2 into polyethylene glycolate mesoporous polydopamine nanoparticles (MPDA-PEG nanoparticles) as a kind of mild photothermal effect assisted nanosystem ( 101 ). In colorectal tumors, nano drugs can release Mn 2+ in the tumor microenvironment, which can be used as immune adjuvants to promote DC maturation and T cell activation.…”
Section: The Significance Of Mno 2 For Cgas-sting ...mentioning
confidence: 99%
“…These probes exhibit better penetration depth and better signal-to-noise ratios of the disease site in FL and PA imaging and minimize the side effects of PTT and PDT. In addition, it has been reported that nanoparticle-based PTT and PDT are able to not only ablate tumors, but also promote systemic antitumor immune activation by releasing tumor antigens and immune-stimulatory molecules [ 77 , 78 , 79 ]. Therefore, nanoprobes for PTT and PDT have great potential for use in anticancer immunotherapy.…”
Section: Nir-ii Fluorescence and Cancer Treatmentmentioning
confidence: 99%